A versatile scaffold contributes to damage survival via sumoylation and nuclease interactions - Sarangi, Prabha; Altmannova, Veronika; Holland, Cory; Bartosova, Zdenka; Hao, Fanfan; Anrather, Dorothea; Ammerer, Gustav; Lee, Sang Eun; Krejci, Lumir; Zhao, Xiaolan (Cell reports, 2014)
DNA repair scaffolds mediate specific DNA and protein interactions in order to assist repair enzymes in recognizing and removing damaged sequences. Many scaffold proteins are dedicated to repairing a particular type of lesion. Here, we show that the budding yeast Saw1 scaffold is more versatile. It helps cells cope with base lesions and protein-DNA adducts through its known function of recruiting the Rad1-Rad10 nuclease to DNA. In addition, it promotes UV survival via a mechanism mediated by its sumoylation. Saw1 sumoylation favors its interaction with another nuclease Slx1-Slx4, and this SUMO-mediated role is genetically separable from two main UV lesion repair processes. These effects of Saw1 and its sumoylation suggest that Saw1 is a multifunctional scaffold that can facilitate diverse types of DNA repair through its modification and nuclease interactions.
Keywords: DNA vazebné proteiny; oprava DNA; Saccharomyces cerevisiae; analýza přežití; Endonucleases; DNA Damage; Survival Analysis; poškození DNA; Saccharomyces cerevisiae - proteiny; Saccharomyces cerevisiae Proteins; sumoylace; endonukleasy; DNA Repair; Sumoylation; DNA-Binding Proteins